THE EFFECT OF TAX AUDITS AND TAX AWARENESS CAMPAIGNS ON THE ENHANCEMENT OF REGIONAL TAX REVENUE IN MAKASSAR CITY WITH PBJT TAXPAYER COMPLIANCE AS AN INTERVENING VARIABLE - Muhammad Zulfiqar; Muspa Muspa; Maryam Nurdin (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
This study aims to analyze the effect of tax audits and tax awareness campaigns on the increase in regional tax revenue, with compliance by taxpayers of the Specific Goods and Services Tax (PBJT) as an intervening variable at the Makassar City Regional Revenue Agency. The research approach utilized a quantitative method with Structural Equation Modeling–Partial Least Squares (SEM-PLS) analysis using the SmartPLS 4 application. The research sample comprised 137 PBJT taxpayers registered with the Makassar City Regional Revenue Agency. The results indicate that tax audits do not have a significant effect on PBJT taxpayers' compliance. Conversely, tax awareness campaigns have a positive and significant effect on PBJT taxpayers' compliance. Neither tax audits nor tax awareness campaigns demonstrate a significant direct effect on the increase in local tax revenue. However, PBJT taxpayers' compliance was found to have a positive and significant effect on the increase in local tax revenue. Mediation analysis revealed that PBJT taxpayers' compliance does not mediate the effect of tax audits on local tax revenue. Still, it does mediate the effect of tax awareness campaigns on the increase in local tax revenue. These findings suggest that strategies to optimize local tax revenue should focus on improving taxpayer compliance through tax education, effective service delivery, and the strengthening of the local tax administration system.